Heat-conducting ceramic-based composite material and preparation method thereof
Through the combination technology of fine-size mesophase bituminous carbon fiber and hafnium zirconium composite ceramic precursor, the problem of insufficient performance of ceramic-based composite materials in extreme environments is solved, and high-performance and lightweight ceramic-based composite materials are achieved.
Patent Information
- Application Number
- CN202411754202.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Existing ceramic matrix composites exhibit insufficient thermal conductivity, mechanical and ablation resistance in extreme environments, and it is difficult to take into account both lightweighting.
A high-thermal fiber preform was woven by finely-sized mesophase asphalt-based carbon fibers, and an interface layer was prepared by chemical vapor deposition. In combination with the precursor impregnation and cracking process, hafnium zirconium composite ceramic precursor was used to prepare hafnium zirconium carbon solid solution as ceramic matrix.
It significantly improves the thermal conductivity, mechanical properties and ablation resistance of ceramic matrix composite materials, while achieving lightweighting of the material.
Smart Images

Figure CN119613135A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to a heat-conducting ceramic-based composite material and a preparation method thereof. Background Art
[0002] PAN-based carbon fiber and mesophase asphalt-based carbon fiber are the two most common carbon fibers in this field, and both have been mass-produced. Compared with PAN-based carbon fiber, mesophase asphalt-based carbon fiber has the characteristics of high thermal conductivity and can achieve an ultra-high thermal conductivity of 800W / m·K. However, the diameter of general mesophase asphalt-based carbon fiber can reach 14μm. Limited by the diameter of the fiber filament, the flexibility is poor. In the process of weaving the preform, it is easy for the filament to break, which leads to a significant impact on the thermal conductivity and mechanical properties of the final ceramic-based composite material. In addition, zirconium carbide and hafnium carbide are two common high-performance ceramics with extremely high melting points, which can be used as ultra-high temperature resistant ceramic matrices. In comparison, hafnium carbide has better ablation resistance than zirconium carbide, but its density is also higher, which is not conducive to lightweighting of materials. Therefore, how to further improve the comprehensive performance of ceramic-based composite materials, ensure their thermal conductivity, mechanical and ablation resistance in extreme environments, and take into account lightweighting, has become a key research issue in this technical field.
[0003] In summary, it is very necessary to provide a thermally conductive ceramic-based composite material and a preparation method thereof. Summary of the invention
[0004] In order to solve one or more technical problems existing in the prior art, the present invention provides a thermally conductive ceramic-based composite material and a preparation method thereof. The method of the present invention uses a thinned mesophase asphalt-based carbon fiber to weave a high thermal conductivity fiber preform, which greatly reduces the fiber breakage rate in the preform, thereby improving the thermal conductivity of the final composite material; at the same time, a new type of hafnium-zirconium composite ceramic precursor is used as a reactant, and high-temperature pyrolysis can obtain a high-performance hafnium-zirconium-carbon solid solution as the matrix of the composite material; the method of the present invention can significantly improve the thermal conductivity and mechanical properties of the composite material, and improve the anti-ablation performance of the composite material, solving the problem of low thermal conductivity, mechanical properties and / or anti-ablation performance of ceramic-based composite materials prepared by traditional technology.
[0005] In a first aspect, the present invention provides a method for preparing a heat-conducting ceramic-based composite material, the method comprising the following steps:
[0006] (1) Weaving thinned mesophase pitch-based carbon fibers into a high thermal conductivity fiber preform;
[0007] (2) preparing an interface layer on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition to obtain a porous carbon / carbon matrix;
[0008] (3) The hafnium-zirconium composite ceramic precursor solution is reacted with the porous carbon / carbon matrix through a precursor impregnation and pyrolysis process to obtain a heat-conducting ceramic-based composite material.
[0009] In a second aspect, the present invention provides a heat conducting ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention.
[0010] Compared with the prior art, the present invention has at least the following beneficial effects:
[0011] (1) The present invention adopts a thinned mesophase asphalt-based carbon fiber with a diameter of 7-9 μm, which greatly improves its flexibility and makes it more braidable without reducing the thermal conductivity and mechanical strength. It is braided into a high thermal conductivity fiber preform, which can significantly reduce the fiber breakage rate in the preform, resulting in a significant improvement in the thermal conductivity and mechanical properties of the heat-conducting ceramic-based composite material.
[0012] (2) The present invention adopts a novel hafnium-zirconium composite ceramic precursor to prepare a hafnium-zirconium carbon solid solution with an adjustable hafnium-zirconium atomic ratio under the premise of achieving atomic-level mixing of hafnium and zirconium. The present invention finds that the hafnium-zirconium carbon solid solution has excellent anti-ablation performance and can greatly improve the anti-ablation performance of the composite material in an oxyacetylene ablation environment. The present invention finds that the hafnium-zirconium carbon solid solution ceramic matrix obtained by using the hafnium-zirconium composite ceramic precursor solution in a ceramic-based composite material has an ultra-high melting point and better anti-ablation performance than a mixed matrix of hafnium carbide and zirconium carbide obtained by using other hafnium-zirconium precursor solutions as reactants, which can greatly improve the temperature resistance and anti-ablation performance of the ceramic-based composite material and is also more conducive to improving the mechanical properties of the ceramic-based composite material.
[0013] (3) In some preferred embodiments of the present invention, after the precursor impregnation and cracking process, the process further includes a step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process. The present invention finds that performing multiple rapid annealing treatments using a Joule heat ultrafast synthesis process can promote matrix recrystallization and densification through uniform high-temperature rapid heat treatment, and can induce redistribution of the ceramic grain boundaries of the ceramic-based composite material to form a grain boundary structure that is more conducive to toughness. Joule heat rapid annealing is beneficial to retaining the fine-grained structure of the material and is more conducive to promoting the formation of a high-temperature stable phase, thereby facilitating the improvement of the mechanical properties, temperature resistance and ablation resistance of the finally prepared ceramic-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a microstructure diagram (SEM diagram) of the heat-conducting ceramic-based composite material prepared in Example 1 of the present invention; Figure 1 It can be seen that a hafnium-zirconium-carbon solid solution is formed in the heat-conducting ceramic-based composite material;
[0015] Figure 2 Schematic diagram of a wedge-shaped high thermal conductivity fiber preform obtained in some specific embodiments of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] In a first aspect, the present invention provides a method for preparing a heat-conducting ceramic-based composite material, the method comprising the following steps:
[0018] (1) Weaving the thin-diameter mesophase pitch-based carbon fibers into a high thermal conductivity fiber preform; in the present invention, for example, a fine weaving and puncturing process is adopted to obtain a high thermal conductivity fiber preform using the thin-diameter mesophase pitch-based carbon fibers as raw materials;
[0019] (2) preparing an interface layer on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition to obtain a porous carbon / carbon matrix; the present invention does not specifically limit the process conditions of the chemical vapor deposition method, and those skilled in the art can routinely select;
[0020] (3) reacting a hafnium-zirconium composite ceramic precursor solution with a porous carbon / carbon matrix through a precursor impregnation and pyrolysis process to obtain a heat-conducting ceramic-based composite material; that is, in step (3), the hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound the porous carbon / carbon matrix, and the heat-conducting ceramic-based composite material is prepared by a precursor impregnation and pyrolysis method.
[0021] The present invention adopts a thinned mesophase asphalt-based carbon fiber with a diameter of 7-9 μm, which greatly improves its flexibility and makes it more braidable without reducing the thermal conductivity and mechanical strength. It is weaved into a high thermal conductivity fiber preform, which can significantly reduce the fiber breakage rate in the preform, resulting in a significant improvement in the thermal conductivity and mechanical properties of the heat-conducting ceramic-based composite material. The invention adopts a novel hafnium-zirconium composite ceramic precursor to prepare a hafnium-zirconium carbon solid solution with an adjustable hafnium-zirconium atomic ratio under the premise of achieving hafnium-zirconium atomic-level mixing; the invention finds that the hafnium-zirconium carbon solid solution has excellent anti-ablation performance and can greatly improve the anti-ablation performance of the composite material in an oxyacetylene ablation environment; the invention finds that the hafnium-zirconium-carbon solid solution ceramic matrix obtained by using the hafnium-zirconium composite ceramic precursor solution in a ceramic-based composite material has an ultra-high melting point and better anti-ablation performance than a mixed matrix of hafnium carbide and zirconium carbide obtained by using other hafnium-zirconium precursor solutions as reactants, can greatly improve the temperature resistance and anti-ablation performance of the ceramic-based composite material, and is also more conducive to improving the mechanical properties of the ceramic-based composite material.
[0022] According to some preferred embodiments, in step (1): the diameter of the thinned mesophase asphalt-based carbon fiber is 7-9 μm, the tensile strength is 2-3 GPa, and the thermal conductivity is 600-800 W / m·K; the fiber diameter of general mesophase asphalt-based carbon fibers can reach 14 μm, which shows poor flexibility. In the subsequent weaving process, the broken wire ratio is high, resulting in reduced mechanical properties and thermal conductivity of the final ceramic-based composite material; generally speaking, the smaller the fiber diameter, the better its flexibility and the higher its weavability; but when the diameter of the mesophase asphalt-based carbon fiber is less than 7 μm, its tensile strength is difficult to meet the weaving requirements, which easily leads to a high broken wire rate in the high thermal conductivity fiber preform; and when the diameter is higher than 9 μm, the fiber flexibility is poor, which also makes the broken wire rate in the high thermal conductivity fiber preform high; the present invention adopts a fiber with a diameter of 7-9 μm, a tensile strength of 2-3 GPa, and a thermal conductivity of 600-800 W / m·K. m·K thin-diameter mesophase asphalt-based carbon fiber, the fiber has high flexibility and high weavability, which is helpful to improve the mechanical properties and thermal conductivity of ceramic-based composite materials; the present invention preferably adopts a thin-diameter mesophase asphalt-based carbon fiber with a diameter of 7-9μm, a tensile strength of 2-3GPa, and a thermal conductivity of 600-800W / m·K to obtain the high thermal conductivity fiber preform. The present invention does not make specific restrictions on the source of the thin-diameter mesophase asphalt-based carbon fiber, which is an existing known material. In the present invention, the thin-diameter mesophase asphalt-based carbon fiber can be from Shaanxi Tiance New Materials Technology Co., Ltd.; in the present invention, for example, a fine weaving and puncturing process is used to weave the thin-diameter mesophase asphalt-based carbon fiber into a high thermal conductivity fiber preform; the present invention does not make specific restrictions on the fine weaving and puncturing process, which can be conventionally selected by technical personnel in the field; and / or the density of the high thermal conductivity fiber preform is 0.7-1.0g / cm3 The present invention adjusts the volume percentage of the thin-diameter mesophase asphalt-based carbon fiber to obtain a density of 0.7-1.0g / cm 3 High thermal conductivity fiber preform.
[0023] According to some preferred embodiments, in step (2): the density of the porous carbon / carbon matrix is 0.9 to 1.2 g / cm 3 ; and / or the interface layer is one or more of a pyrolytic carbon interface layer, a boron nitride interface layer, and a silicon carbide interface layer; the present invention does not specifically limit the process conditions for depositing the interface layer, which is a conventional technique in the art, and can be deposited by using chemical vapor deposition technology, by adjusting the volume percentage and / or thickness of the interface layer, which is preferably a pyrolytic carbon interface layer, so that the density of the porous carbon / carbon matrix after the interface layer is deposited is 0.9 to 1.2 g / cm 3 .
[0024] According to some preferred embodiments, in step (3): the preparation of the hafnium-zirconium composite ceramic precursor solution is as follows: propyl hafnate (i.e., tetrapropyl hafnate) and propyl zirconate (i.e., n-propyl zirconate) are mixed uniformly with xylene, and then ninhydrin is added as a ligand and a phenolic epoxy vinyl ester resin is added and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere environment of 5°C to 10°C for 100 to 150 minutes to obtain the hafnium-zirconium composite ceramic precursor solution; the present invention does not specifically limit the phenolic epoxy vinyl ester resin, and a directly purchased product or The products synthesized by the existing methods are all available; the present invention obtains a novel hafnium-zirconium composite ceramic precursor solution in which hafnium and zirconium are mixed at the atomic level by mixing hafnium propyl ester and zirconate and then undergoing coordination reaction and co-hydrolysis reaction; the polyhafnium zirconoxane in the hafnium-zirconium composite ceramic precursor solution has hafnium and zirconium on the same main chain, thus achieving atomic-level mixing; in the present invention, since hafnium and zirconium are associated elements, the two have similar properties and a large atomic diffusion coefficient, so crystal atomic replacement can be achieved; and the present invention uses ninhydrin as a ligand, which has three binding sites, compared with the use of ligands such as acetylacetone , which can ensure that the distribution of hafnium propyl ester and zirconate propyl ester is more uniform, so that the ratio of hafnium to zirconium in the main chain of polyhafnium zirconoxane is more accurate, and effectively avoid excessive aggregation of a certain component, resulting in a large difference in the atomic components of hafnium zirconium carbon solid solution in different regions. In addition, the present invention takes into account the difference in molar mass of hafnium and zirconium, and by extending the reaction time in the low-temperature argon environment, it can ensure that the reaction is sufficient and uniform, and also ensure that the ratio of hafnium to zirconium in the main chain of polyhafnium zirconoxane is more accurate. The present invention finds that it is the atomic carbon nanotube prepared by the above method that can ensure a more accurate ratio of hafnium to zirconium in the main chain of polyhafnium zirconoxane. A hafnium-zirconium composite ceramic precursor solution mixed with a certain grade is solidified and subjected to high-temperature cracking treatment to obtain a hafnium-zirconium-carbon solid solution as a ceramic matrix in a ceramic-based composite material. The present invention finds that the hafnium-zirconium-carbon solid solution ceramic matrix obtained by using the hafnium-zirconium composite ceramic precursor solution in a ceramic-based composite material has an ultra-high melting point and better ablation resistance than a mixed matrix of hafnium carbide and zirconium carbide obtained by using other hafnium-zirconium precursor solutions as reactants, can greatly improve the temperature resistance and ablation resistance of the ceramic-based composite material, and is also more conducive to improving the mechanical properties of the ceramic-based composite material.
[0025] According to some preferred embodiments, the molar amount of the ninhydrin is 0.27 to 1.5 times, preferably 0.5 to 0.8 times, of the sum of the molar amounts of the hafnate propyl ester and the zirconate propyl ester; and / or the molar amount of the phenolic epoxy vinyl ester resin is 0.9 to 5 times, preferably 1.5 to 3 times, of the sum of the molar amounts of the hafnate propyl ester and the zirconate propyl ester.
[0026] According to some preferred embodiments, the solid content of the hafnium-zirconium composite ceramic precursor solution is 40-60%, and the viscosity is 30-80 mPa·s; in the present invention, the solid content is the mass percentage of the remaining part of the hafnium-zirconium composite ceramic precursor solution after solidification of the hafnium-zirconium composite ceramic precursor solution; in the present invention, the amount of the hafnium propyl ester and the zirconium propyl ester is such that the molar ratio of hafnium in the hafnium propyl ester to zirconium in the zirconate propyl ester is (0.1-99.9): (0.1-99.9); the amount of the xylene is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 40-60%, and the viscosity is 30-80 mPa·s; the molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution is (0.1-99.9): (0.1-99.9); since the densities of zirconium carbide and hafnium carbide are 6.6 g / cm 3 Left and right and 12.8g / cm 3 The density difference between the two is large, so the present invention can adjust the hafnium-zirconium atomic ratio to obtain a series of hafnium-zirconium-carbon solid solutions; and / or the hafnium-zirconium composite ceramic precursor solution forms a hafnium-zirconium-carbon solid solution as a ceramic matrix in the precursor impregnation and cracking process; for example, Figure 1 As shown, the microstructure of the heat-conducting ceramic-based composite material prepared by the present invention shows that a hafnium-zirconium-carbon solid solution is formed in the heat-conducting ceramic-based composite material.
[0027] The present invention does not specifically limit the impregnation, curing and cracking conditions specifically used in the precursor impregnation, curing and cracking process, and those skilled in the art can make routine selections. The present invention uses a hafnium-zirconium composite ceramic precursor solution as a reactant, and fills the hafnium-zirconium composite ceramic precursor solution into the pores by vacuum and pressure impregnation. After heating at 150-350°C, the ceramic precursor can be completely cured, and after a high-temperature cracking process, the above-mentioned impregnation-curing-cracking process is repeated to finally obtain a heat-conducting ceramic-based composite material.
[0028] According to some preferred embodiments, step (4) comprises the following sub-steps:
[0029] (a) placing a porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and immersing it for 10 to 360 minutes, filling the hafnium-zirconium composite ceramic precursor solution into the internal pores, and obtaining a material impregnated with the hafnium-zirconium composite ceramic precursor solution; preferably, the impregnation is vacuum impregnation and pressure impregnation; the present invention does not specifically limit the process parameters of vacuum impregnation and pressure impregnation, which are well known to those skilled in the art and can be carried out using conventional parameters;
[0030] (b) curing the material impregnated with the hafnium-zirconium composite ceramic precursor solution, for example, curing under an inert atmosphere such as nitrogen and heating at 150-350° C., so that the hafnium-zirconium composite ceramic precursor solution in the pores can be cross-linked and cured, and then placing the cured material in a reaction device, sealing, evacuating, and introducing an inert gas such as nitrogen at a flow rate of, for example, 500-5000 sccm, and pyrolyzing at 1500-1800° C., preferably 1600-1800° C. for 10-600 min; preferably, the curing is curing at 150-350° C. for 10-360 min; in the present invention, the heating rate to 150-350° C. and / or 1500-1800° C. can be, for example, 1-10° C. / min;
[0031] (c) After the cracking reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped, and the temperature is restored to atmospheric pressure; in the present invention, the rate of the temperature reduction can be, for example, 1 to 5°C / minute;
[0032] (d) Repeating steps (a) to (c) at least once, for example, multiple times (twice or more), preferably 1 to 10 times.
[0033] According to some preferred embodiments, in step (3), after the precursor impregnation and cracking process is performed, the process further includes a step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process; the Joule heat ultrafast synthesis process is performed in a Joule ultrafast heating device (Joule ultrafast heating device), and the heating rate of each annealing treatment is 180 to 260°C / s (for example, 180°C / s, 190°C / s, 200°C / s, 210°C / s, 220°C / s, 2 30℃ / s, 240℃ / s, 250℃ / s or 260℃ / s), the annealing temperature is 1600-2000℃ (for example, 1600℃, 1700℃, 1800℃, 1900℃ or 2000℃), the holding time of each annealing is 2-5min (for example, 2, 3, 4 or 5min), and after the holding time is completed, it is naturally cooled to room temperature and then the next annealing treatment is performed; the number of annealing treatments is 3-5 times (for example, 3, 4 or 5 times).
[0034] The present invention preferably includes the step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process after the precursor impregnation and cracking process. The present invention finds that performing multiple rapid annealing treatments using a Joule heat ultrafast synthesis process can promote matrix recrystallization and densification through uniform high-temperature rapid heat treatment, and can induce grain boundary redistribution of the ceramic-based composite material to form a ceramic grain boundary structure that is more conducive to toughness. Joule heat rapid annealing is beneficial to retaining the fine-grained structure of the material and is more conducive to promoting the formation of a high-temperature stable phase, thereby helping to improve the mechanical properties, temperature resistance and ablation resistance of the finally prepared ceramic-based composite material.
[0035] According to some preferred embodiments, in step (1), the high thermal conductivity fiber preform is a pointed wedge-shaped high thermal conductivity fiber preform; in the present invention, the structure of the pointed wedge-shaped high thermal conductivity fiber preform is as follows: Figure 2 As shown; the preparation of the pointed wedge-shaped high thermal conductivity fiber preform is: mixing the thin-diameter mesophase asphalt-based carbon fiber and the PAN-based carbon fiber to obtain a thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth, and then using a lamination and stitching process to make the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth into a pointed wedge-shaped high thermal conductivity fiber preform; in the present invention, when the pointed wedge-shaped high thermal conductivity fiber preform is used, the obtained thermal conductive ceramic-based composite material is in a pointed wedge shape.
[0036] Since the fiber diameter of general mesophase asphalt-based carbon fiber can reach 14μm, it shows poor flexibility and is difficult to meet large bending. As a result, the existing preforms woven with general mesophase asphalt-based carbon fiber and / or PAN-based carbon fiber are usually flat preforms. However, the ceramic-based composite materials currently made using this conventional structural preform are in the shape of a flat plate. This conventional shape cannot meet the application requirements in certain specific scenarios. In order to obtain a ceramic-based composite material of a specific shape, the traditional preparation technology usually prepares a flat ceramic-based composite material first, and then processes it into a specific shape. This method that requires reprocessing leads to a large waste of ceramic-based composite materials and fiber breakage and fiber discontinuity. The problem, ultimately leads to deficiencies in thermal conductivity, ablation resistance and / or mechanical properties of the ceramic-based composite material of a specific shape prepared by traditional technology.
[0037] The present invention preferably designs a fiber preform of a novel structure, that is, a pointed wedge-shaped high thermal conductivity fiber preform is used as a preform for a ceramic-based composite material. The main structural feature of the pointed wedge-shaped high thermal conductivity fiber preform in the present invention is that along a certain fiber direction, the surface of the preform gradually becomes pointed, and the geometric shape is a pointed wedge (a shape in which one end of the preform is pointed and the other end is thick). One end of the pointed wedge-shaped high thermal conductivity fiber preform of the present invention is a pointed end region, and the other end is a thick end region. The present invention finds that the use of such a pointed wedge-shaped preform can obtain a directly integrated pointed wedge-shaped ceramic-based composite material. The pointed wedge-shaped ceramic-based composite material has better structural adaptability and functionality in specific application scenarios, and the pointed wedge-shaped structure can improve the stress distribution and local strengthening effect of the material. In some applications, the pointed wedge shape is helpful for optimizing fluid flow. ization, reducing friction resistance, especially in the fields of aerospace, power machinery, etc., the pointed wedge-shaped structure can effectively improve the flow state of airflow and liquid flow, improve energy efficiency, and can better disperse the concentrated area of external force, reduce crack propagation, and improve fatigue resistance under high temperature and high pressure environment; the present invention can realize the weaving of the pointed wedge-shaped high thermal conductivity fiber preform by mixing the thin-diameter mesophase asphalt-based carbon fiber and the carbon fiber, which gives full play to the high flexibility and high thermal conductivity of the thin-diameter mesophase asphalt-based carbon fiber, while the simple PAN-based and general asphalt-based carbon fiber cannot meet the design requirements due to their poor flexibility; and the present invention can realize the controllable adjustment of the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material by regulating the volume ratio of the thin-diameter mesophase asphalt-based carbon fiber to the carbon fiber in the pointed wedge-shaped high thermal conductivity fiber preform.
[0038] The present invention preferably uses a pointed wedge-shaped high thermal conductivity fiber preform to directly integrate and form a pointed wedge-shaped ceramic-based composite material, which can take into account both fiber continuity and cost economy, and better ensure the thermal conductivity and mechanical properties of the ceramic-based composite material. This is also something that cannot be achieved by using a ceramic-based composite material made of a conventional structural preform and then processing it into a pointed wedge-shaped product after molding. This is because this method of first molding the ceramic-based composite material and then processing it into a product of a specific shape will cause the fibers in the tip area of the product to no longer be continuous. At the same time, there is a large waste in the preparation process, and there is a problem of insufficient thermal conductivity, ablation resistance and mechanical properties of the prepared ceramic-based composite material.
[0039] According to some preferred embodiments, the diameter of the thinned mesophase asphalt-based carbon fiber used in the pointed wedge-shaped high thermal conductivity fiber preform is 7-9 μm, the tensile strength is 2-3 GPa, and the thermal conductivity is 600-800 W / m·K, indicating that it has excellent flexibility and can meet the requirements of nearly 180° bending in the tip area of the pointed wedge-shaped high thermal conductivity fiber preform without breaking, thereby realizing the weaving of the pointed wedge-shaped high thermal conductivity fiber preform.
[0040] According to some preferred embodiments, in the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth, the thin-diameter mesophase asphalt-based carbon fiber and the PAN-based carbon fiber are vertically distributed, that is, when the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth is mixed, the thin-diameter mesophase asphalt-based carbon fiber and the PAN-based carbon fiber are perpendicular to each other; and / or the surface density of the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth is 300-400 g / m 2 When the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth is mixed in the present invention, the ratio of the thin-diameter mesophase asphalt-based carbon fiber to the PAN-based carbon fiber can be adjusted to meet the subsequent weaving of a pointed wedge-shaped high thermal conductivity fiber preform having a specific volume ratio of thin-diameter mesophase asphalt-based carbon fiber to PAN-based carbon fiber.
[0041] According to some preferred embodiments, the lamination and stitching process is: first fold the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth in a direction perpendicular to the thin-diameter mesophase asphalt-based carbon fiber, and then stack and stitch multiple (two or more) folded thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth to obtain a pointed wedge-shaped high thermal conductivity fiber preform; in the present invention, when laminating, the tip of the folded thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth corresponds to the tip, and the thick end corresponds to the thick end, and then PAN-based carbon fiber is used to stitch the multiple folded thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloths into one; the present invention does not make specific restrictions on the stitching method used, and technicians in this field can make conventional choices, for example, an orthogonal stitching method can be selected; the present invention does not make specific restrictions on the number of thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloths used in the stacking, and technicians in this field can make conventional choices based on the thickness requirements of the pointed wedge-shaped high thermal conductivity fiber preform.
[0042] According to some preferred embodiments, the volume ratio of the thinned mesophase pitch-based carbon fibers to the PAN-based carbon fibers in the pointed wedge-shaped high thermal conductivity fiber preform is (1-3): (1-3).
[0043] In the second aspect, the present invention provides a thermally conductive ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention; the thermally conductive ceramic-based composite material prepared by the present invention has a hafnium-zirconium-carbon solid solution as a ceramic matrix, and has the advantages of high thermal conductivity, excellent mechanical properties and anti-ablation properties, which are manifested in a significant improvement in room temperature thermal conductivity and mechanical properties, and a significant reduction in online ablation rate under oxyacetylene ablation environment.
[0044] According to some preferred embodiments, the density of the thermal conductive ceramic matrix composite material is 3.0 to 5.0 g / cm 3and / or the thermal conductivity of the thermally conductive ceramic-based composite material at room temperature is greater than or equal to 120 W / (m·K), preferably greater than or equal to 210 W / (m·K), the tensile strength at room temperature is greater than or equal to 100 MPa, preferably greater than or equal to 146 MPa, and the oxyacetylene wire ablation rate is less than or equal to 1×10 -3 mm / s.
[0045] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.
[0046] Example 1
[0047] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, the raw material is fine-diameter mesophase asphalt-based carbon fiber with a diameter of 7μm, a tensile strength of 2.4GPa, and a thermal conductivity of 800W / m·K. The density is 0.8g / cm 3 A flat plate-shaped high thermal conductivity fiber preform.
[0048] ② Preparation of porous carbon / carbon matrix: A pyrolytic carbon interface layer was prepared on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition method to obtain a porous carbon / carbon matrix with a density of 1.0 g / cm 3 porous carbon / carbon matrix.
[0049] ③ Preparation of a hafnium-zirconium composite ceramic precursor solution: In the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s; the hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 3:1) in xylene, and then adding ninhydrin as a ligand (propyl hafnium, zirconium The hafnium zirconium composite ceramic precursor solution is prepared by mixing hafnium propyl ester and ninhydrin in a molar ratio of 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) to obtain a mixed solution, and reacting the mixed solution under an argon atmosphere at 5° C. for 120 minutes to obtain an atomically uniformly mixed hafnium zirconium composite ceramic precursor solution. The amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s.
[0050] ④ Preparation of heat-conducting ceramic-based composite materials: A hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound a porous carbon / carbon matrix, and a flat-plate-shaped heat-conducting ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium The material impregnated with the composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated multiple times until a density of 3.8 g / cm was obtained. 3 Flat plate-shaped heat-conducting ceramic matrix composite material.
[0051] The thermal conductivity of the thermal conductive ceramic matrix composite material prepared in this embodiment is measured to be 210 W / (m·K) at room temperature, the tensile strength is 146 MPa at room temperature, and the linear ablation rate is 0.53×10 -3 mm / s.
[0052] Example 2
[0053] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, the raw material is fine-diameter mesophase asphalt-based carbon fiber with a diameter of 9μm, a tensile strength of 2.4GPa, and a thermal conductivity of 800W / m·K. The preform is woven to obtain a density of 0.8g / cm 3 A flat plate-shaped high thermal conductivity fiber preform.
[0054] ② Preparation of porous carbon / carbon matrix: A pyrolytic carbon interface layer was prepared on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition method to obtain a porous carbon / carbon matrix with a density of 1.0 g / cm 3 porous carbon / carbon matrix.
[0055] ③ Preparation of a hafnium-zirconium composite ceramic precursor solution: In the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s; the hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 3:1) in xylene, and then adding ninhydrin as a ligand (propyl hafnium, zirconium The hafnium zirconium composite ceramic precursor solution is prepared by mixing hafnium propyl ester and ninhydrin in a molar ratio of 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) to obtain a mixed solution, and reacting the mixed solution under an argon atmosphere at 5° C. for 120 minutes to obtain an atomically uniformly mixed hafnium zirconium composite ceramic precursor solution. The amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s.
[0056] ④ Preparation of heat-conducting ceramic-based composite materials: A hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound a porous carbon / carbon matrix, and a flat-plate-shaped heat-conducting ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium The material impregnated with the composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated multiple times until a density of 3.8 g / cm was obtained. 3 Flat plate-shaped heat-conducting ceramic matrix composite material.
[0057] The thermal conductivity of the thermal conductive ceramic matrix composite material prepared in this embodiment is measured to be 226 W / (m·K) at room temperature, the tensile strength is 163 MPa at room temperature, and the linear ablation rate is 0.49×10 -3 mm / s.
[0058] Example 3
[0059] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, the raw material is fine-diameter mesophase asphalt-based carbon fiber with a diameter of 5μm, a tensile strength of 2.4GPa, and a thermal conductivity of 800W / m·K. The preform is woven to obtain a density of 0.8g / cm 3 A flat plate-shaped high thermal conductivity fiber preform.
[0060] ② Preparation of porous carbon / carbon matrix: A pyrolytic carbon interface layer was prepared on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition method to obtain a porous carbon / carbon matrix with a density of 1.0 g / cm 3 porous carbon / carbon matrix.
[0061] ③ Preparation of a hafnium-zirconium composite ceramic precursor solution: In the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s; the hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 3:1) in xylene, and then adding ninhydrin as a ligand (propyl hafnium, zirconium The hafnium zirconium composite ceramic precursor solution is prepared by mixing hafnium propyl ester and ninhydrin in a molar ratio of 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) to obtain a mixed solution, and reacting the mixed solution under an argon atmosphere at 5° C. for 120 minutes to obtain an atomically uniformly mixed hafnium zirconium composite ceramic precursor solution. The amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s.
[0062] ④ Preparation of heat-conducting ceramic-based composite materials: A hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound a porous carbon / carbon matrix, and a flat-plate-shaped heat-conducting ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium The material impregnated with the composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated multiple times until a density of 3.8 g / cm was obtained. 3 Flat plate-shaped heat-conducting ceramic matrix composite material.
[0063] The thermal conductivity of the thermal conductive ceramic matrix composite material prepared in this embodiment is measured to be 85 W / (m·K) at room temperature, the tensile strength is 101 MPa at room temperature, and the linear ablation rate is 0.74×10 -3 mm / s.
[0064] Example 4
[0065] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, the mesophase asphalt-based carbon fiber with a diameter of 10 μm, a tensile strength of 2.4 GPa, and a thermal conductivity of 800 W / m·K is used as the raw material to weave a high thermal conductivity fiber preform with a density of 0.8 g / cm 3 A flat plate-shaped high thermal conductivity fiber preform.
[0066] ② Preparation of porous carbon / carbon matrix: A pyrolytic carbon interface layer was prepared on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition method to obtain a porous carbon / carbon matrix with a density of 1.0 g / cm 3 porous carbon / carbon matrix.
[0067] ③ Preparation of a hafnium-zirconium composite ceramic precursor solution: In the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s; the hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 3:1) in xylene, and then adding ninhydrin as a ligand (propyl hafnium, zirconium The hafnium zirconium composite ceramic precursor solution is prepared by mixing hafnium propyl ester and ninhydrin in a molar ratio of 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) to obtain a mixed solution, and reacting the mixed solution under an argon atmosphere at 5° C. for 120 minutes to obtain an atomically uniformly mixed hafnium zirconium composite ceramic precursor solution. The amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s.
[0068] ④ Preparation of heat-conducting ceramic-based composite materials: A hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound a porous carbon / carbon matrix, and a flat-plate-shaped heat-conducting ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium The material impregnated with the composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated multiple times until a density of 3.8 g / cm was obtained. 3 Flat plate-shaped heat-conducting ceramic matrix composite material.
[0069] The thermal conductivity of the thermal conductive ceramic matrix composite material prepared in this embodiment is measured to be 111 W / (m·K) at room temperature, the tensile strength is 119 MPa at room temperature, and the linear ablation rate is 0.68×10 -3 mm / s.
[0070] Example 5
[0071] ① Preparation of high thermal conductivity fiber preform: Using fine weaving puncture process, the mesophase asphalt-based carbon fiber with a diameter of 14μm, a tensile strength of 2.4GPa, and a thermal conductivity of 800W / m·K is used as the raw material to weave a high thermal conductivity fiber preform with a density of 0.8g / cm 3 A flat plate-shaped high thermal conductivity fiber preform.
[0072] ② Preparation of porous carbon / carbon matrix: A pyrolytic carbon interface layer was prepared on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition method to obtain a porous carbon / carbon matrix with a density of 1.0 g / cm 3 porous carbon / carbon matrix.
[0073] ③ Preparation of a hafnium-zirconium composite ceramic precursor solution: In the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s; the hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 3:1) in xylene, and then adding ninhydrin as a ligand (propyl hafnium, zirconium The hafnium zirconium composite ceramic precursor solution is prepared by mixing hafnium propyl ester and ninhydrin in a molar ratio of 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) to obtain a mixed solution, and reacting the mixed solution under an argon atmosphere at 5° C. for 120 minutes to obtain an atomically uniformly mixed hafnium zirconium composite ceramic precursor solution. The amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s.
[0074] ④ Preparation of heat-conducting ceramic-based composite materials: A hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound a porous carbon / carbon matrix, and a flat-plate-shaped heat-conducting ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium The material impregnated with the composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated multiple times until a density of 3.8 g / cm was obtained. 3 Flat plate-shaped heat-conducting ceramic matrix composite material.
[0075] The thermal conductivity of the thermal conductive ceramic matrix composite material prepared in this embodiment is measured to be 96 W / (m·K) at room temperature, the tensile strength is 108 MPa at room temperature, and the linear ablation rate is 0.70×10 -3 mm / s.
[0076] It can be seen from the above examples 1 to 5 that, compared with example 1, the diameter of the mesophase pitch-based carbon fiber used in example 2 is increased from 7 μm to 9 μm. As the diameter becomes larger, the flexibility becomes worse, and the broken wire rate is slightly reduced, resulting in the thermal conductivity of the ceramic matrix composite material being increased from 210 W / (m·K) to 226 W / (m·K), the tensile strength being increased from 146 MPa to 163 MPa, and the line ablation rate being increased from 0.53×10 -3 mm / s is reduced to 0.49×10 -3 Compared with Example 1, the diameter of the mesophase pitch-based carbon fiber used in Example 3 is reduced from 7 μm to 5 μm. The smaller diameter helps to improve flexibility, but the tensile strength it can withstand is reduced, and its broken wire rate is greatly increased, resulting in the thermal conductivity of the ceramic matrix composite material being reduced from 210 W / (m·K) to 85 W / (m·K), the tensile strength being reduced from 146 MPa to 101 MPa, and the wire ablation rate being reduced from 0.53×10 -3 mm / s increased to 0.74×10-3 Compared with Example 1, the diameter of the mesophase pitch-based carbon fiber used in Example 4 is increased from 7 μm to 10 μm. As the diameter increases, the flexibility decreases, and the broken wire rate increases, resulting in the thermal conductivity of the ceramic matrix composite material decreasing from 210 W / (m·K) to 111 W / (m·K), the tensile strength decreasing from 146 MPa to 119 MPa, and the line ablation rate decreasing from 0.53×10 -3 mm / s increased to 0.68×10 - 3 Compared with Example 1, the diameter of the mesophase pitch-based carbon fiber used in Example 5 is increased from 7 μm to 14 μm. Due to the larger diameter, the flexibility is extremely poor, and the broken wire rate is very high, resulting in the thermal conductivity of the ceramic matrix composite material being reduced from 210 W / (m·K) to 96 W / (m·K), the tensile strength being reduced from 146 MPa to 108 MPa, and the line ablation rate being reduced from 0.53×10 -3 mm / s increased to 0.70×10 -3 mm / s.
[0077] Embodiments 6 to 10
[0078] Examples 6 to 11 are basically the same as Example 1. The specific process parameters and the properties of the ceramic-based composite materials finally prepared are shown in Table 1 below. The other preparation processes are the same as those in Example 1.
[0079] Table 1
[0080]
[0081]
[0082]
[0083] It can be seen from Table 1 above that, compared with Example 1, the atomic ratio of hafnium and zirconium in the hafnium-zirconium composite ceramic precursor solution used in Example 6 is increased from 3:1 to 10:1, so that the proportion of hafnium in the hafnium-zirconium-carbon solid solution is significantly increased, resulting in a density of the ceramic matrix composite material from 3.8 g / cm 3 Increased to 4.3g / cm 3 The oxyacetylene line ablation rate also increased from 0.53×10 -3 mm / s decreased to 0.21×10 - 3 mm / s, and the ablation resistance is enhanced. Compared with Example 1, the hafnium-zirconium atomic ratio of the hafnium-zirconium composite ceramic precursor solution used in Example 7 is reduced from 3:1 to 1:1, so that the proportion of hafnium in the hafnium-zirconium-carbon solid solution is significantly reduced, resulting in a density of the ceramic matrix composite material from 3.8 g / cm 3 Reduced to 3.55g / cm 3The oxyacetylene line ablation rate also increased from 0.53×10 -3 mm / s increased to 0.61×10 -3 mm / s, and the ablation resistance is reduced. Compared with Example 1, the hafnium-zirconium atomic ratio of the hafnium-zirconium composite ceramic precursor solution used in Example 8 is reduced from 3:1 to 1:3, so that the proportion of hafnium in the hafnium-zirconium-carbon solid solution is significantly reduced, resulting in a density of the ceramic matrix composite material from 3.8 g / cm 3 Reduced to 3.26g / cm 3 The oxyacetylene line ablation rate also increased from 0.53×10 -3 mm / s increased to 0.77×10 -3 mm / s, and the ablation resistance is reduced. Compared with Example 1, the hafnium-zirconium atomic ratio of the hafnium-zirconium composite ceramic precursor solution used in Example 9 is reduced from 3:1 to 1:10, so that the proportion of hafnium in the hafnium-zirconium-carbon solid solution is significantly reduced, resulting in a density of the composite material from 3.8 g / cm 3 Reduced to 3.11g / cm 3 The oxyacetylene line ablation rate also increased from 0.53×10 -3 mm / s increased to 0.92×10 -3 mm / s, the ablation resistance is reduced. Compared with Example 1, the density of the porous carbon / carbon matrix used in Example 10 is increased from 1.0 g / cm 3 Increased to 1.1g / cm 3 , which reduces the internal pore volume and the content of hafnium-zirconium-carbon solid solution in the thermal conductive ceramic matrix composite material, resulting in the density of the composite material from 3.8 g / cm 3 Reduced to 3.64g / cm 3 The oxyacetylene line ablation rate also increased from 0.53×10 -3 mm / s increased to 0.59×10 -3 mm / s, the ablation resistance is reduced. Compared with Example 1, the density of the porous carbon / carbon matrix used in Example 11 is increased from 1.0 g / cm 3 Reduced to 0.9g / cm 3 , which increases the internal pore volume and the content of hafnium-zirconium-carbon solid solution in the thermal conductive ceramic matrix composite material, resulting in the density of the composite material from 3.8 g / cm 3 Increased to 3.97g / cm 3 The oxyacetylene line ablation rate also increased from 0.53×10 -3 mm / s decreased to 0.47×10 -3 mm / s, and the anti-ablation performance is enhanced.
[0084] Example 12
[0085] ①Same as step ① of Example 1.
[0086] ②Same as step ② of Example 1.
[0087] ③ is the same as step ③ of Example 1.
[0088] ④ Preparation of heat-conducting ceramic-based composite materials: A hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound a porous carbon / carbon matrix, and a flat-plate-shaped heat-conducting ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium The material impregnated with the composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated multiple times until a density of 3.8 g / cm was obtained. 3 The flat-plate heat-conducting ceramic-based composite material is prepared. After the precursor impregnation and cracking process is completed, the flat-plate heat-conducting ceramic-based composite material is further annealed three times using a Joule heat ultrafast synthesis process; wherein the Joule heat ultrafast synthesis process is carried out in a Joule ultra-fast heating device, the heating rate of each annealing treatment is 200°C / s, the annealing treatment is carried out in a nitrogen atmosphere, the annealing temperature is 1800°C, and the insulation time for each annealing at 1800°C is 3 minutes. After the insulation is completed, it is naturally cooled to room temperature before the next annealing treatment is carried out.
[0089] The thermal conductivity of the thermal conductive ceramic matrix composite material finally obtained in this embodiment is measured to be 210 W / (m·K) at room temperature, the tensile strength is 155 MPa at room temperature, and the linear ablation rate is 0.38×10 -3 mm / s.
[0090] Embodiment 13
[0091] Example 13 is substantially the same as Example 12, except that:
[0092] ④ Preparation of heat-conducting ceramic-based composite materials: A hafnium-zirconium composite ceramic precursor solution is used as a reactant to compound a porous carbon / carbon matrix, and a flat-plate-shaped heat-conducting ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with a hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium The material impregnated with the composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated multiple times until a density of 3.8 g / cm was obtained. 3 The flat-plate heat-conducting ceramic-based composite material is annealed after the precursor impregnation and cracking process is completed; wherein the annealing treatment is carried out in a nitrogen atmosphere, the annealing temperature is 1800°C, the holding time at 1800°C is 9 minutes, and the heating rate to 1800°C is 10°C / min.
[0093] It was measured that the thermal conductivity of the thermally conductive ceramic-based composite material finally prepared in this embodiment was 210 W / (m·K) at room temperature, and the tensile strength was 93 MPa at room temperature.
[0094] Embodiment 14
[0095] ① Weaving fine-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth: The fine-diameter mesophase pitch-based carbon fiber and PAN-based carbon fiber are mixed to obtain fine-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth, so that the fine-diameter mesophase pitch-based carbon fiber and PAN-based carbon fiber are vertically distributed, and the surface density of the fine-diameter mesophase pitch-based carbon fiber / carbon fiber bidirectional cloth is 365g / m 2 The fine-diameter mesophase pitch-based carbon fiber used is a fine-diameter mesophase pitch-based carbon fiber with a diameter of 7 μm, a tensile strength of 2.4 GPa, and a thermal conductivity of 800 W / m·K.
[0096] ② Preparation of a pointed wedge-shaped high thermal conductivity fiber preform: A stacking and stitching process is adopted to obtain a pointed wedge-shaped high thermal conductivity fiber preform by weaving a thin-diameter intermediate phase asphalt-based carbon fiber / carbon fiber bidirectional cloth, specifically: firstly, the thin-diameter intermediate phase asphalt-based carbon fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the thin-diameter intermediate phase asphalt-based carbon fiber, and then a plurality of folded thin-diameter intermediate phase asphalt-based carbon fiber / carbon fiber bidirectional cloths are stacked and stitched to obtain a pointed wedge-shaped high thermal conductivity fiber preform; during the stacking, the tip of the folded thin-diameter intermediate phase asphalt-based carbon fiber / carbon fiber bidirectional cloth corresponds to the tip, and the thick end corresponds to the thick end, and then the stacked plurality of folded thin-diameter intermediate phase asphalt-based carbon fiber / carbon fiber bidirectional cloths are stitched into one body by using PAN-based carbon fiber to obtain a pointed wedge-shaped high thermal conductivity fiber preform; the volume ratio of the thin-diameter intermediate phase asphalt-based carbon fiber to the PAN-based carbon fiber in the obtained pointed wedge-shaped high thermal conductivity fiber preform is 2:1, and the density of the pointed wedge-shaped high thermal conductivity fiber preform is 0.75 g / cm 3 .
[0097] ③ Preparation of wedge-shaped porous carbon / carbon matrix: A pyrolytic carbon interface layer was prepared on the fiber surface of the wedge-shaped high thermal conductivity fiber preform by chemical vapor deposition method, and a density of 0.95 g / cm 3 The pointed wedge-shaped porous carbon / carbon matrix.
[0098] ④ Preparation of a hafnium-zirconium composite ceramic precursor solution: In the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 3:1, the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%, and the viscosity is 55 mPa·s; the hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 3:1) in xylene, and then adding ninhydrin as a ligand (propyl hafnium, zirconium The hafnium zirconium composite ceramic precursor solution is prepared by mixing hafnium propyl ester and ninhydrin in a molar ratio of 3:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin is 3:1:10) to obtain a mixed solution, and reacting the mixed solution under an argon atmosphere at 5° C. for 120 minutes to obtain an atomically uniformly mixed hafnium zirconium composite ceramic precursor solution. The amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 50% and the viscosity is 55 mPa·s.
[0099] ⑤ Preparation of thermal conductivity ceramic-based composite materials: using a hafnium zirconium composite ceramic precursor solution as a reactant, compounding a wedge-shaped profiling porous carbon / carbon matrix, and preparing a wedge-shaped thermal conductivity ceramic-based composite material with a hafnium zirconium carbon solid solution as a ceramic matrix through a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the wedge-shaped profiling porous carbon / carbon matrix in a hafnium zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the hafnium zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200Pa, and the pressurized impregnation pressure is 1.5MPa; then The material impregnated with the hafnium-zirconium composite ceramic precursor solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was cracked at 1600°C for 240 min. After the cracking reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The impregnation-curing-cracking process was repeated many times until a density of 3.8 g / cm was obtained. 3 Sharp wedge-shaped heat-conducting ceramic matrix composite material.
[0100] The thermal conductivity of the sharp wedge-shaped heat-conducting ceramic-based composite material prepared in this embodiment is measured to be 202 W / (m·K) at room temperature, the tensile strength is 134 MPa at room temperature, and the linear ablation rate is 0.57×10 -3 mm / s.
[0101] Comparative Example 1
[0102] Comparative Example 1 A flat plate-shaped heat-conducting ceramic-based composite material was obtained by the same method as in Example 1, and then machined into a pointed wedge-shaped heat-conducting ceramic-based composite material.
[0103] The thermal conductivity of the wedge-shaped thermal conductive ceramic matrix composite material prepared in this comparative example is 75 W / (m·K) at room temperature, the tensile strength is 96 MPa at room temperature, and the linear ablation rate is 0.81×10 -3 mm / s.
[0104] Comparative Example 2
[0105] ①Same as step ① of Example 14.
[0106] ② Preparation of a flat-plate high thermal conductivity fiber preform: A lamination and stitching process is adopted to obtain a flat-plate high thermal conductivity fiber preform by weaving a thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth. Specifically, a plurality of thin-diameter mesophase asphalt-based carbon fibers / carbon fiber bidirectional cloths are stacked and stitched together to obtain a flat-plate high thermal conductivity fiber preform; the volume ratio of the thin-diameter mesophase asphalt-based carbon fibers to the PAN-based carbon fibers in the obtained flat-plate high thermal conductivity fiber preform is 2:1, and the density of the flat-plate high thermal conductivity fiber preform is 0.75 g / cm 3 ; The flat-plate-shaped high thermal conductivity fiber preform obtained in step ② is used to replace the wedge-shaped high thermal conductivity fiber preform in Example 14 to carry out the same subsequent steps ③, ④ and ⑤ as in Example 14.
[0107] The thermal conductivity of the flat plate-shaped heat-conducting ceramic matrix composite material prepared in this comparative example is measured to be 206 W / (m·K) at room temperature, the tensile strength is 138 MPa at room temperature, and the linear ablation rate is 0.55×10 -3 mm / s.
[0108] In this comparative example, the flat plate-shaped heat-conducting ceramic-based composite material is machined into a pointed wedge-shaped heat-conducting ceramic-based composite material, and the thermal conductivity of the pointed wedge-shaped heat-conducting ceramic-based composite material at room temperature is measured to be 72 W / (m·K), the tensile strength at room temperature is 91 MPa, and the linear ablation rate is 0.85×10 -3 mm / s.
[0109] Although the performance of the flat-plate heat-conducting ceramic-based composite material prepared in this comparative example is basically consistent with the pointed wedge-shaped heat-conducting ceramic-based composite material prepared in Example 14, when the flat-plate heat-conducting ceramic-based composite material prepared in this comparative example is processed into a pointed wedge-shaped heat-conducting ceramic-based composite material by traditional machining, this traditional method will cause the fibers in the tip area of the product to no longer be continuous, resulting in a significant decrease in the thermal conductivity, ablation resistance and mechanical properties of the pointed wedge-shaped heat-conducting ceramic-based composite material.
[0110] Comparative Example 3
[0111] ①Same as step ① of Example 1.
[0112] ②Same as step ② of Example 1.
[0113] ③ Preparation of hafnium-zirconium composite ceramic precursor solution: In the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 3:1, and the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%. The hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium ester and propyl zirconate (in an amount such that the molar ratio of hafnium in hafnium ester to zirconium in zirconate is 3:1) in xylene, and then adding acetylacetone as a ligand (hafnium ester The hafnium zirconium composite ceramic precursor solution is prepared by mixing propyl hafnium ester, propyl zirconate and acetylacetone in a molar ratio of 3:1:3) and allyl phenolic resin (the molar ratio of propyl hafnium ester, propyl zirconate and allyl phenolic resin is 3:1:10) and uniformly mixing to obtain a mixed solution, reacting the mixed solution in an argon atmosphere at 15° C. for 70 minutes to obtain a molecular-level mixed hafnium-zirconium composite ceramic precursor solution, and the amount of xylene used is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 50%.
[0114] ④ Preparation of thermal conductive ceramic-based composite materials: The hafnium-zirconium composite ceramic precursor solution obtained in step ③ is used as a reactant to compound the porous carbon / carbon matrix, and a thermal conductive ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process includes a specific impregnation-curing-pyrolysis process as follows: placing the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium composite ceramic precursor is placed in a pre-curing process. The material impregnated with the solution was cured in a nitrogen atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with nitrogen inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 5°C / min, cooled to room temperature, the nitrogen inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated many times until a density of 3.8 g / cm was obtained. 3 A flat plate-shaped heat-conducting ceramic matrix composite material with hafnium carbide and zirconium carbide as a ceramic matrix.
[0115] The thermal conductivity of the flat plate-shaped heat-conducting ceramic matrix composite material prepared in this comparative example is measured to be 210 W / (m·K) at room temperature, the tensile strength is 138 MPa at room temperature, and the linear ablation rate is 1.1×10 -3 mm / s.
[0116] It can be seen from the comparison between Example 1 and Comparative Example 3 that by using the hafnium-zirconium composite ceramic precursor solution of the present invention as an impregnation solution, a hafnium-zirconium-carbon solid solution ceramic matrix can be obtained in the ceramic-based composite material, which is beneficial to improving the ablation resistance and mechanical properties of the ceramic-based composite material.
[0117] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a heat-conducting ceramic-based composite material, characterized in that: The method comprises the following steps: (1) Weaving thinned mesophase pitch-based carbon fibers into a high thermal conductivity fiber preform; (2) preparing an interface layer on the fiber surface of the high thermal conductivity fiber preform by chemical vapor deposition to obtain a porous carbon / carbon matrix; (3) The hafnium-zirconium composite ceramic precursor solution is reacted with the porous carbon / carbon matrix through a precursor impregnation and pyrolysis process to obtain a heat-conducting ceramic-based composite material.
2. The preparation method according to claim 1, characterized in that: In step (1): The diameter of the thinned mesophase pitch-based carbon fiber is 7-9 μm, the tensile strength is 2-3 GPa, and the thermal conductivity is 600-800 W / m·K; Weaving the thinned mesophase pitch-based carbon fibers into a high thermal conductivity fiber preform using a fine weaving and puncturing process; and / or The density of the high thermal conductivity fiber preform is 0.7-1.0 g / cm 3 .
3. The preparation method according to claim 1, characterized in that: In step (2): The density of the porous carbon / carbon matrix is 0.9-1.2 g / cm 3 ; and / or The interface layer is one or more of a pyrolytic carbon interface layer, a boron nitride interface layer, and a silicon carbide interface layer.
4. The preparation method according to claim 1, characterized in that: In step (3): The hafnium-zirconium composite ceramic precursor solution is prepared by mixing hafnium propyl ester and zirconate evenly with xylene, then adding ninhydrin as a ligand and adding phenolic epoxy vinyl ester resin and mixing evenly to obtain a mixed solution, and reacting the mixed solution in an argon atmosphere at 5°C to 10°C for 100 to 150 minutes to obtain the hafnium-zirconium composite ceramic precursor solution.
5. The preparation method according to claim 4, characterized in that: The molar amount of the ninhydrin is 0.5 to 0.8 times the sum of the molar amounts of the hafnium propyl ester and the zirconate propyl ester; and / or The molar amount of the phenolic epoxy vinyl ester resin is 1.5 to 3 times the sum of the molar amounts of the propyl hafnate and the propyl zirconate.
6. The preparation method according to claim 4, characterized in that: The hafnium-zirconium composite ceramic precursor solution has a solid content of 40-60% and a viscosity of 30-80 mPa·s; The molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution is (0.1-99.9): (0.1-99.9); and / or The hafnium-zirconium composite ceramic precursor solution forms a hafnium-zirconium-carbon solid solution as a ceramic matrix in the precursor impregnation and cracking process.
7. The preparation method according to claim 1, characterized in that: Step (4) includes the following sub-steps: (a) impregnating the porous carbon / carbon matrix in a hafnium-zirconium composite ceramic precursor solution for 10 to 360 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution; preferably, the impregnation is vacuum impregnation and pressure impregnation; (b) curing the material impregnated with the hafnium-zirconium composite ceramic precursor solution, and then placing it in a reaction device, sealing it, evacuating it, introducing an inert gas, and cracking it at 1500-1800° C. for 10-600 min; preferably, the curing is performed at 150-350° C. for 10-360 min; (c) after the cracking reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped, and the pressure is restored to atmospheric pressure; (d) Repeating steps (a) to (c) at least once, preferably 1 to 10 times.
8. The preparation method according to any one of claims 1 to 7, characterized in that In step (3), after the precursor impregnation and cracking process is performed, the method further includes the step of performing multiple annealing treatments using a Joule heat ultrafast synthesis process; The Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, the heating rate of each annealing treatment is 180-260°C / s, the annealing temperature is 1600-2000°C, the insulation time of each annealing is 2-5min, and after the insulation is completed, it is naturally cooled to room temperature before the next annealing treatment is carried out; The annealing treatment is performed 3 to 5 times.
9. The thermally conductive ceramic-based composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: In step (1): The high thermal conductivity fiber preform is a wedge-shaped high thermal conductivity fiber preform; The preparation of the pointed wedge-shaped high thermal conductivity fiber preform is as follows: thin-diameter mesophase asphalt-based carbon fiber and PAN-based carbon fiber are mixed to obtain thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth, and then the thin-diameter mesophase asphalt-based carbon fiber / carbon fiber bidirectional cloth is made into a pointed wedge-shaped high thermal conductivity fiber preform by a lamination and stitching process.
10. The thermal conductive ceramic-based composite material prepared by the preparation method according to any one of claims 1 to 9; Preferably, the density of the thermal conductive ceramic matrix composite material is 3.0 to 5.0 g / cm 3 ; and / or Preferably, the thermal conductivity of the thermal conductive ceramic matrix composite material at room temperature is greater than or equal to 120 W / (m·K), the tensile strength at room temperature is greater than or equal to 100 MPa, and the oxyacetylene wire ablation rate is less than or equal to 1×10 -3 mm / s.
Citation Information
Patent Citations
Interface-modified ceramic-based composite material and preparation method thereof
CN115710134A
Dispersing type heat conduction ceramic-based composite material and preparation method thereof
CN117303926A
Secondary polymer layered impregnated tile
US6955853B1
Medium / high-entropy ceramic material and fiber-toughened ceramic-based composite material, and preparation methods therefor and use thereof
WO2023174160A1
Cited By
Method for preparing ceramic-based composite material through ultra-fast infiltration and pyrolysis and application of ceramic-based composite material
CN121426582A